HARRY POTTER’S SUPEREGO IN CONTROLLING HIS ANGER IN JK. ROWLING’S HARRY POTTER AND THE ORDER OF THE PHOENIX NOVEL (2003): A PSYCHOANALYTIC APPROACH - Agustin, Kharisma Asa (2010)
The purpose of this study is to analyze J. K. Rowling’s Harry Potter and the Order of the Phoenix based on its structural elements and the personality of the major character based on psychoanalytic approach. The writer employs qualitative method. In this method, the writer uses two data sources, namely primary and secondary data sources. The primary data source is J. K. Rowling’s Harry Potter and the Order of the Phoenix novel. The secondary data sources are the books about psychoanalytic theory, references from internet related about Harry Potter and the Order of the Phoenix novel, and other sources related to the analysis. The method of data collection is library research and the technique of data collection is descriptive technique. The results of the research are as follow. First, the conclusion from the structural analysis of the novel. There are a close relationship between each plot, character and characterization, setting of time and place, point of view, style and tone, and the theme of the story. Those elements are supporting each other and cannot be separated. Second, Harry Potter experiences conflicts between his personality systems. This conflict happens after the existence of two conditions, those are the unpleasant events and unfair conditions. His conflicts make him angry. Some reactions of his anger pushed him to do bad things. He uses superego to reduce his anger and its reaction. The superego functioned by Harry in two systems, self-criticism and self-observing.